2006
DOI: 10.1371/journal.pbio.0050005
|View full text |Cite|
|
Sign up to set email alerts
|

The RNA-Binding Protein KSRP Promotes Decay of β-Catenin mRNA and Is Inactivated by PI3K-AKT Signaling

Abstract: β-catenin plays an essential role in several biological events including cell fate determination, cell proliferation, and transformation. Here we report that β-catenin is encoded by a labile transcript whose half-life is prolonged by Wnt and phosphatidylinositol 3-kinase–AKT signaling. AKT phosphorylates the mRNA decay-promoting factor KSRP at a unique serine residue, induces its association with the multifunctional protein 14-3-3, and prevents KSRP interaction with the exoribonucleolytic complex exosome. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
186
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(199 citation statements)
references
References 54 publications
12
186
1
Order By: Relevance
“…Silencing experiments demonstrated that both Akt1 and Akt2 are required for DM-induced maturation of miR-1a, miR-133b and miR-206 (compare the expression of mature and primary miRNA in Figures 1c and d). In agreement with a role of AKT in myomiR maturation, expression of a membrane-bound myristoilated and constitutively active form of Akt2 (myr-AKT2 30 ) strongly enhanced the expression of myomiRs in C2C12 cells cultured in DM without affecting the expression of the corresponding pri-miRNAs (Figures 1e and f).…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…Silencing experiments demonstrated that both Akt1 and Akt2 are required for DM-induced maturation of miR-1a, miR-133b and miR-206 (compare the expression of mature and primary miRNA in Figures 1c and d). In agreement with a role of AKT in myomiR maturation, expression of a membrane-bound myristoilated and constitutively active form of Akt2 (myr-AKT2 30 ) strongly enhanced the expression of myomiRs in C2C12 cells cultured in DM without affecting the expression of the corresponding pri-miRNAs (Figures 1e and f).…”
Section: Resultssupporting
confidence: 79%
“…26 KSRP distinct functions are regulated by different protein kinases, including MAPK p38, PI3K/AKT and ATM. 8,29,30 An unresolved issue is whether a specific signaling pathway regulates only a single KSRP function (i.e. affecting either mRNA decay or miRNA maturation) or is able to induce a dynamic change between KSRP functions in order to produce relevant phenotypes in a specific cellular context.…”
mentioning
confidence: 99%
“…However, it is possible that these additional activation events are consequent of the crosstalk between the Wnt pathway and MAPK or PI3K, described elsewhere [37,38]. Recently, Gherzi et al reported that the half-life of β-catenin mRNA is prolonged not only by Wnt but also by PI3K-Akt signalling, adding further complexity to the potential mechanisms by which insulin/IGF-1 could interact with Wnt signalling [39]. With the data available, we cannot dismiss the possibility that these different signalling events could converge to activate beta cell proliferation.…”
Section: Discussionmentioning
confidence: 98%
“…Little is known regarding the regulation of Sfrp5 expression. Of note, insulin, IGF-1 and other hormonal factors have been shown to activate the canonical Wnt signalling by increasing nuclear β-catenin content and binding of β-catenin/TCF to Wnt target gene promoters [39][40][41]. Thus, it is plausible that IGFBP3 and SFRP5 are two of the molecules mediating the crosstalk between the Wnt and insulin/IGF-1 signalling pathways at the level of pancreatic beta cells in the context of diet-induced obesity.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the components of translational machinery, RNA-binding proteins are also aberrantly expressed in tumors, including PTB (He et al, 2007), HuR (Lopez de Silanes et al, 2003), KH domain-containing protein, and hnRNPD among others (Gouble et al, 2002), with a direct correlation between abnormal expression of a particular RNA-binding protein and tumor formation (CRD-BP) in breast tissue (Tessier et al, 2004). Furthermore, many RNA-binding proteins have been reported to be direct targets of Akt, including YB-1 (Evdokimova et al, 2006), the tumor suppressor Pdcd4 (Palamarchuk et al, 2005), BRF1 (Benjamin et al, 2006) and KSRP (Gherzi et al, 2006), thus linking the Akt pathway to mRNA silencing, degradation, apoptosis and the Wnt signaling pathway through the promotion of the stabilization of b-catenin mRNA, respectively.…”
Section: Introductionmentioning
confidence: 99%